On the use of high-level taxonomic names - Hedges, S. Blair (Zootaxa, 2011)
Asher & Helgen (2010) recently proposed some rules for naming animal taxa above the family level—names that are currently unregulated. They suggested that strict priority be used as a criterion for high-level names and that such priority be based on group content rather than the procedure used for low-level taxa, anchored to constituent taxa. Authorship of a high-level name thus may vary in a complex way depending on content. While it is true that taxonomic codes are always in need of improvement, the lack of regulation of high-level names has not caused major problems. Originality, priority, stability, and other common sense considerations usually come to play in a process that can be described as community consensus. Their proposed system would lead to less stability because names would lack both permanent anchors (e.g., types) and permanent authors, and would be based on something (group content) susceptible to change with time. Furthermore, name selection may frequently conflict with common usage, leading to confusion  and instability. An example of the problems with these rules is their preferred name for the order containing tenrecs and golden moles, Tenrecoidea, which has a long history of different meanings (content). Instead, the most commonly used name, Afrosoricida, is also preferred because it does not have that confusing history and has a more typical suffix (-a) for a mammalian order.